Diseño y simulación con ISE (Identitiy Services Engine) para mitigar accesos no autorizados a una red corporativa - López Mendoza, Carlos Hans (2017)
This document describes all the procedures to carry out the protection of a corporate network vulnerabilities and mitigate threats through the Identity Services Engine using standard protocols such as 802.1x access level. Through Cisco ISE providing analysis of threat mitigation, network visibility, extensive policy enforcement, robust guest experiences, and then documenting the inputs and statistics of the results obtained reporting across networks can easily validate compliance for audits and regulatory requirements, robust historical and real-time reporting for all services. Logs all activities and offers real-time dashboard metrics of all users and endpoints connecting to the network with ISE.